ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI USAHATANI PADI SAWAH DI KECAMATAN TAJINAN ANALYSIS OF THE FACTORS AFFECTING WASTE IN TAJINAN DISTRICT - Muhammadanil Wasil (Program Studi Agribisnis, 2019)
AbstractThe purpose of this research is for knowing about profit and R/C ratio value of soybean farming. Also for analiyzed about price efficiency for soybean farming in Purwodadi subdistrict, Grobogan Regency the Central of Java. This research has been done in the District of Purwodadi, Grobogan Regency using random sampling methods with 50 sample of soybean farmers. Analysis of data used descriptive analysis and analysis of frontier production function and Maximum Likelihood Estimation(MLE) methods. The result of this research showed that the value of R/C ratio are 2,0 its mean that this farming are feasible cultivated. And the production factor thats influence for soybean farming are all of the fertilizer (Urea, TSP, and Phonska). The soybean farmer in allocating the factor of production is not efficient because the NPM/PX value of all the fertilizer are <1. So, the soybean farming in the district of Purwodadi have not been pricely efficient yet.Keywords: price efficiency, factor of production